Development Strategy of Indonesian Palm Oil Industrial Cluster Based International Trade Connectivity - Sapta Raharja; Setiadi Djohar; Dwi Aryanthi (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2021)
Indonesia is the largest producer and the exporter of palm oil in the world which has three palm oil industrial cluster (POIC) areas that are Sei Mangkei (North Sumatera), Dumai (Riau), and Maloy (East Kalimantan). To carry out the delivery of palm oil products to the destination countries, the Palm oil from the three POICs must be transshipment in Malaysia and Singapore. In line with this issues, a strategy to develop the POIC based international connectivity need to be done. This study aims to identify the actual conditions of POIC Indonesia, to determine the factors (internal and external) that influence the development of POIC, and to formulate priority strategy for developing POIC Indonesia. These are needed so that Indonesia can become a hub port of international trade especially in Asia. This research uses